PERAN MOTIVASI TERHADAP KEBERLANGSUNGAN USAHA UMKM MAK INDAH DI KOTA BENGKAYANG - Milenium, Gadis Nagata; Salfarini, Eligia Monixa (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national and regional economy, including in Bengkayang City. However, the sustainability of MSMEs is often faced with various challenges, one of which is the motivation factor of the owner or manager. This study aims to analyze the role of motivation in the sustainability of the Mak Indah MSME business in Bengkayang City. Using the [FILL IN YOUR RESEARCH METHOD, e.g.: qualitative with case study] approach, data were collected through [FILL IN YOUR DATA COLLECTION METHOD, e.g.: in-depth interviews, observations, and documentation studies] at the Mak Indah MSME. The results of the study indicate that [FILL IN YOUR KEY FINDINGS, e.g.: intrinsic and extrinsic motivation of Mak Indah MSME owners has a significant role in overcoming challenges and encouraging innovation, which ultimately contributes to business sustainability]. These findings provide practical implications for MSME owners and policy makers in designing strategies to increase motivation in order to achieve better business sustainability